Command economy in practice (Economic and Political Thought, 2016)
The article is a follow-up to the analysis of theoretical premises of command/planned economy and presents practical consequences of the implementationof Marxism and Russian Bolshevism. The author discusses the phenomenaresulting from practical use of the ideology starting with a statement aboutthe “economic expansion drive” – a major determinant of decision-makingfactors in the command system. The economic expansion drive, which wasa result of the system’s belligerent attitudes, made communist authoritiestake economic decisions in compliance with political criteria, irrespective ofeconomic rationalism. As a result, all the efficiency indices in that systemwere poorer than in market economy. Practical effects of that also consistedin deformation of investment processes and defective consumer goods marketmanifesting itself in the form of invariable supply-demand disequilibrium.Political motives behind economic decisions also led to excessive use ofresources and intensification of the “deficit” phenomenon in all the economicsectors. Practical consequences of the deficit were disastrous for companies’efficiency and people’s financial situation. Finally, the author illustrates histheses with some data showing that from the 1970s the command system wassliding down an inclined plane and, at its end, it eventually collapsed.